Contos e encantos maranhenses no teatro de animação: uma proposta artística interdisciplinar - SILVA, Geisa Letícia (2020)
The present research, with the proposal to investigate the artistic and pedagogical potential of the Theater of Animation in the school, as well as its insertion from the production of shows, emphasizing the legends of Maranhão. In addition, there search proposes the valorization of the local cultural identity from the presentation of the cultural manifestations of Maranhão, using the Theater of Animation. Action research methodology were used. The target audience was the elementary school students at UEB Henrique de La Roque Almeida in São Luís - MA. The research field was restricted to a group that carried out the staging, emphasizing research and the teaching-learning process. In addition to the process of making puppets, writing dramatizations, rehearsals were carried out, along with workshops on body expression, theatrical games and vocal technique. The culmination took place with a critical analysis of the dramatization presentation process and a survey of the receptivity of the school community, as well as the involvement of students with regard to the development of animation techniques and the skills of writing and orality through the texts produced. All stages were recorded through vídeos, fotos and questionnaires for analysis and evaluation.